Continuous fast focusing in a trapezoidal void channel based on bidirectional isotachophoresis in a wide pH range - Stastna, Miroslava; Slais, Karel (Electrophoresis, 2015)
This study concentrates on development of instrumentation for focusing and separation of analytes in continuous flow. It is based on bidirectional ITP working in wide pH range with separation space of closed void channel of trapezoidal shape and continuous supply of sample. The novel instrumentation is working with electrolyte system formulated previously and on the contrary to devices currently available, it allows preparative separation and concentration of cationic, anionic, and amphoteric analytes simultaneously and in wide pH range. The formation of sharp edges at zone boundaries as well as low conductivity zones are avoided in suggested system and thus, local overheating is eliminated allowing for high current densities at initial stages of focusing. This results in high focusing speed and reduction of analysis time, which is particularly advantageous for separations performed in continuous flow systems. The closed void channel is designed to avoid basic obstacles related to liquid leakage, bubbles formation, contacts with electrodes, channel height and complicated assembling. The performance of designed instrumentation and focusing dynamics were tested by using colored low molecular mass pH indicators for local pH determination, focusing pattern, and completion. In addition, feasibility and separation efficiency were demonstrated by focusing of cytochrome C and myoglobin. The collection of fractions at instrument output allows for subsequent analysis and identification of sample components that are concentrated and conveniently in form of solution for further processing. Since the instrumentation operates with commercially available simple defined buffers and compounds without need of carrier ampholytes background, it is economically favorable.
Keywords: izotachoforéza; Models, Chemical; Trapezoidal void channel; Hydrogen-Ion Concentration; chemické modely; Feasibility Studies; Proteins; Wide pH range; barvicí látky; Coloring Agents; studie proveditelnosti; Equipment Design; Myoglobin; design vybavení; koncentrace vodíkových iontů; Bidirectional isotachophoresis; Focusing; myoglobin; Isotachophoresis